Silenced Voices: Institutional Responses to Bullying of Deans in Canadian and Australian Universities - Bosetti, Lynn; Heffernan, Troy (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2025)
In this paper, we share testimonies from interviews with 29 faculty deans from universities across Canada and Australia who have been targeted by bullies, and we examine how their institutions responded. Often silenced, we expose the consequences of institutional (in)actions on the identity and well-being of these leaders and document the impact of inadequate policies and procedures that deans are trusted to protect and support them. These stories combine to create a collective force calling for institutional courage to address incivility and bullying, as well as to challenge the culture that enables and reinforces it. We conclude with recommendations that institutions can implement to proactively protect and support deans to mitigate bullying in higher education.